Risk factors for the recurrence of an intracranial saccular aneurysm following endovascular treatment - Huang, De-Zhang (Oncotarget, 2017)
BACKGROUND: This study was aimed to determine risk factors for the recurrence of an intracranial saccular aneurysm (ISA) following endovascular treatment. The findings will help medical professionals to identify patients having a high risk of ISA recurrence and assist them in developing appropriate follow-up plans. RESULTS: During the follow-up period, 12.6% of the patients (83/658) experienced recurrent ISAs. An analysis of related factors, including gender, age, hypertension, diabetes mellitus, smoking, tumor size, width of the aneurysm neck, the presence or absence of a rupture, the volume embolization ratio (VER), the application or nonapplication of a stent, and follow-up time, revealed that a tumor size > 10 mm in diameter, wide-necked aneurysms, an anterior communicating or middle cerebral artery aneurysm, an aneurysm rupture, a VER < 20%, the absence of stent assistance, and follow-up time were high-risk factors for the recurrence of ISAs. MATERIALS AND METHODS: We retrospectively reviewed the records of 658 patients who underwent endovascular treatment for ISAs from January 2010 through December 2014. Multivariable logistic regression was performed on the candidates’ risk factors, which were identified via univariable screening analysis. CONCLUSIONS: Smoking, a large tumor size, a wide-necked aneurysm, an anterior communicating or middle cerebral artery aneurysm, an aneurysm rupture, a VER < 20%, and an absence of stent assistance are significant risk factors for the postoperative recurrence of an aneurysm. Strict follow-up plans should be created for ISA patients having these high-risk factors.